Photocatalytic Degradation of Acid Blue 113 Over Iron Modified Vermiculite Using Solar Light - Revathy, Selvaraj; Palanichamy, Muthaihpillai; Jeyalakshmi, R. (Asian Journal of Chemistry, 2012)
Natural vermiculite was enriched with iron by incipient wet method, and characterized by XRD and FT-IR. The structure of vermiculite was retained after modification. The modified vermiculite was used as the catalyst for the solar light assisted degradation of acid blue113, a very commonly used dye in textile industry. The degradation was carried out by varying amount of H2O2 (15 mM - 75 mM) for 250 mL of 50 ppm dye solution. The degradation was monitored by measuring absorbance at 566 nm. The complete degradation of the dye required 240 min. The degradation was more than 90 % solar light assisted and removal of dye by adsorption was minimum (5 %). Complete mineralization of dye was evident from total organic carbon analysis. In support of total organic carbon results, the percentage chemical oxygen demand (% COD) increased with an increase in irradiation time. The optimum pH range for degradation was 2.9 to 3.5. Dissolution of iron from vermiculite was proved negligible. It was established that any textile effluent carrying acid blue 113 will be effectively mineralized using low cost naturally occurring eco-friendly vermiculite.